PENERAPAN STRATEGI ROTATING TRIO EXCHANGE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 LENGAYANG KABUPATEN PESISIR SELATAN - Handayani, Sri; Rismen, Sefna; Anggraini, Villia (Pendidikan Matematika, 2013)
The research was background by the student comprehension of mathematical concept are still low at SMPN 1 Lengayang. Research purposes to determine whether students comprehension of mathematical concepts using Strategy Rotating Trio Exchange better than students with an comprehension of mathematical concepts by using conventional learning in class VIII SMPN 1 Lengayang. Type of research to design experiments by using Randomized for Subject. The research instrument was a test, the reliability r11 = 0.71. The data analysis technique used is the one party t final test, tcount = 2,30 > ttable = 1,64, then the hypothesis is accepted, So it can be concluded that the studentsâ comprehension of mathematical concepts by using strategies Rotating Trio Exhange better than students comprehension of mathematical concepts by using conventional learning in class VIII SMPN1 Lengayang.